Protective effect of taurine against alendronate-induced gastric damage in rats - ŞENER, GÖKSEL (WILEY, 2005)
Alendronate (ALD) causes serious gastrointestinal adverse effects. The aim of this study was to investigate whether taurine (TAU), a semi-essential amino acid and an antioxidant, improves the alendronate-induced gastric injury. Rats were administered 20 mg/kg ALD by gavage for 4 days, either alone or following treatment with TAU (50 mg/kg, i.p.). On the last day of treatment, following drug administration, pylorus ligation was performed and 2 h later, rats were killed and stomachs were removed. Gastric acidity and tissue ulcer index values, lipid peroxidation and glutathione (GSH) levels, myeloperoxidase (MPO) activity as well as the histologic appearance of the stomach tissues were determined. Chronic oral administration of ALD induced significant gastric damage, increasing lipid peroxidation, MPO activity and collagen content, as well as decreasing tissue GSH levels. Treatment with TAU prevented the damage and also the changes in biochemical parameters. Findings of the present study suggest that ALD induces oxidative gastric damage by a local irritant effect, and that TAU ameliorates this damage by its antioxidant and/or membrane-stabilizing effects.
Keywords: alendronate; glutathione; lipid peroxidation; myeloperoxidase; taurine; MUCOSAL INJURY; MECHANISMS; BISPHOSPHONATES; DYSFUNCTION; CISPLATIN; TOXICITY; KIDNEY; HEART